PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN PADA PT TUNAS JASA MANDIRI - Gunawan, Hendra; Realize, Realize (LPPM Universitas Putera Batam, 2021)
The intense competition and business development require companies to fullfill what consumer wants by providing qualitys services and adequate facilities. The research objective was to determined the effectt of services quality and facilities in customers saticfaction at PT Tunas Jasa Mandiri, either partialy or simultaniously. Data collections was done by distributing questionaires to respondent, the sampling technique uses was saturated sampling of 102 respondent. The data quality test use in this study are validity and reliabillity tests, as well as the multiple linear reggression analysist and determination coeficient analysis, while the hypothessis testing in this study use the T tests and the F tests. The statistical tests show that variables of service quality, facilities and customer satisfaction are normally distributed, the independent variable do not occur multicollinearity or heteroscedasticity. The result of determination is 75.4%. From the t and f tests can be conclude that the quality of service and facilities partially had a significant effects on customer saticfaction, and the quality of service and facilities simultaneously had a significant effects on customer satisfactions at PT Tunas Jasa Mandiri